2021
DOI: 10.1177/0969733021999763
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ self-assessed moral courage and related socio-demographic factors

Abstract: Background: Nurses need moral courage to ensure ethically good care. Moral courage is an individual characteristic and therefore it is relevant to examine its association with nurses’ socio-demographic factors. Objective: To describe nurses’ self-assessed level of moral courage and its association with their socio-demographic factors. Research design: Quantitative descriptive cross-sectional study. The data were collected with Nurses’ Moral Courage Scale and analyzed statistically. Participants and research co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 50 publications
4
30
4
Order By: Relevance
“…The results showed that demographic characteristics did not contribute to explaining variance in conscientiousness and moral courage significantly. In line with the results of the present study, the results of Hauhio et al 's study showed that there was no relationship between age, work experience, and highest degree with moral courage [30]. No significant correlation was found between the level of conscientiousness and job factors in the study by Kwiatosz-Muc et al [84].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results showed that demographic characteristics did not contribute to explaining variance in conscientiousness and moral courage significantly. In line with the results of the present study, the results of Hauhio et al 's study showed that there was no relationship between age, work experience, and highest degree with moral courage [30]. No significant correlation was found between the level of conscientiousness and job factors in the study by Kwiatosz-Muc et al [84].…”
Section: Discussionsupporting
confidence: 87%
“…Moral courage and conscientiousness are characteristics that are related to individual and organizational factors [10,30]. Individual factors include socio-demographic factors such as work experience [31,32], level of education [33,34], age [33,35], frequency of challenging situations [31], marital status [32] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Moral courage is "the golden mean" between cowardice and rashness, with the former indicating irrational fear and the latter thoughtlessness. 16,31,33,34 In the health care context, research about moral courage has been scarce, although it has increased during the past decade, particularly among nurses 33,[35][36][37] and nurse students. [38][39][40][41] The characteristics of a morally courageous nurse 14,30,32,33,37,38,42 and the background variables associated with moral courage have been described in previous literature.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40][41] The characteristics of a morally courageous nurse 14,30,32,33,37,38,42 and the background variables associated with moral courage have been described in previous literature. 36,41 Morally courageous nurses are ethically sensitive, willing to risk themselves for the benefit of others and to act according to their own conscience. 37,[43][44][45] They feel responsibility for others 14,32,45 and possess confidence in situations requiring moral courage 14,43 and are confident in their own ethical principles 41 and value base.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation